Protease from Courgette (Luffa Acutangula L (Roxb)): Isolation, Purification, and Some Characteristics - Mike Permata Sari; Dwirini Retno Gunarti; Mohamad Sadikin (Jurnal Sumberdaya Hayati, 2019)
The Courgette or oyong (Luffa acutangula L. (Roxb)) is member of Cucurbitaceae mainly used as vegetable. Beside used as vegetables, courgette aslo used as keratolytic agent. This fact is supposed that this vegetables contain protease. This research is succeed to purified courgette’s protease by four step. That was precipitate by 70% ammonium sulphate saturation, purification using DEAE cellulose ion exchange chromatography and gel filtration chromatography using sephadex G-100 and G-75. Purified courgette’s protease had 81,922 U/mg for specific activity and 34 kDa molecular weight. This enzyme had the characteristic such as activated optimally at 37oC, pH 7 and 10 minute duration time. This enzyme activity can decrease by PMSF and H2O2, its remarkable that courgette protease is serine protease and had the thiol group in its structure. The ability to digest food proteins materials like boiled meat and boiled white egg by courgette protease proves that the courgette protease enzyme is could be used in enzyme replacement therapy in mild digestion problem.